Does female participation in strategic decision‐making roles matter for corporate social responsibility performance?. (4th February 2022) - Bose, Sudipta; Hossain, Sarowar; Sobhan, Abdus; Handley, Karen
Abstract: We examine the association between female participation in strategic decision‐making roles and corporate social responsibility (CSR) performance using a sample of United States firms from 2001 to 2018. Female participation in strategic decision‐making roles is measured using: (i) the female presence in different positions on the board of directors, such as female board member, independent board member, chairperson and audit committee member; and (ii) the female presence in top management roles, such as chief executive officer (CEO) and chief financial officer (CFO). We find that female participation in strategic decision‐making roles is positively associated with CSR performance. In investigating the 'tokenism' aspect of female participation on the board, our results contradict the 'tokenism' argument for appointing females to boards, instead supporting their real influence on CSR performance. These findings are important to regulators, policy makers, company management and other stakeholders with an interest in how increased female participation in strategic decision‐making roles influences CSR performance.